The Effect of Using ESA Method on Students’ Reading Comprehension in Descriptive Text at the First Grade at Sumatera Thawalib Islamic Boarding School in Academic Year 2023/2024 - Yovi, Febri Yonanda; Roza, Veni; Melanie, Melyan; Irwandi, Irwandi (Education Achievement: Journal of Science and Research, 2025)
The purpose of this study was to determine how Sumatera Thawalib Islamic Boarding School Parabek students' reading comprehension of descriptive texts was affected by the Engage-Study-Activate (ESA) strategy. The study discovered issues like When the teacher asks the class to share their thoughts in English, the students' first intention is to remain silent. Second, a lack of vocabulary prevents pupils from understanding the material. Thirdly, reading comprehension levels among students are subpar. Finally, when teachers employ traditional techniques like teacher-centered learning strategies, children get less attention. A quantitative methodology using a quasi-experimental design was used in the research, with 29 students in the experimental class (1.5) and 31 students in the control class (1.6). A multiple-choice test was employed as the research instrument to gauge gains in reading comprehension. Data analysis was done with SPSS 26. Results showed that, when compared to conventional approaches, the ESA method considerably increased reading comprehension scores, as shown by a p-value less than 0.05. The conclusion, it was found that the ESA method was a more successful teaching strategy that significantly improved student comprehension and engagement. In conclusion, students’ reading comprehension in Sumatera Thawalib Parabek is significantly improved by the ESA approach as compared to traditional ways.